2021
DOI: 10.2147/dmso.s297368
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Prevalence of Impotence among Diabetic Patients in Northwestern Hospitals of Nefasit, Eretria

Abstract: Background Impotence incidence in patients with elevated glycemic index valuesis 30%–69.01%. While impotence is very prevalent among diabetic men, the condition is mostly left unaddressed and needs assessment and care. Impotence can influence the quality of social, mental, leisure, and sexual life, and can contribute to broken relationships, depression, and reduced self-esteem. The goal of the present work was to research the commonness and determinants of impotence among diabetic patients in hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The factors associated with erectile dysfunction in this study are age ≥ 45, inadequate physical activities (< 600 MET), and being rich. This study showed that being older (≥ 45 years) is 12.39 times more likely to develop erectile dysfunction which is in line with most studies [ 51 , 53 , 54 , 56 , 65 ]. This can be due to age-related physiological changes like decreased testosterone production in older men [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The factors associated with erectile dysfunction in this study are age ≥ 45, inadequate physical activities (< 600 MET), and being rich. This study showed that being older (≥ 45 years) is 12.39 times more likely to develop erectile dysfunction which is in line with most studies [ 51 , 53 , 54 , 56 , 65 ]. This can be due to age-related physiological changes like decreased testosterone production in older men [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with research conducted in the Amhara region of Ethiopia 85.5% [ 41 ], in Ghana 81.8% [ 52 ] and Indonesia 84.4% [ 53 ]. Moreover, this study found a higher prevalence compared to researches done in most areas of Ethiopia(54.3-69.9%) [ 19 , 39 , 54 , 55 ], Eritrea 74.2% [ 56 ] ,Tanzania 55.1% [ 50 ], recent systematic review done in Africa 71.45% [ 57 ], Western Asia 62.2% [ 58 ], China 64.2% [ 40 ], South America 74.6% [ 59 ], Bangladesh(45.3-60.2%) [ 35 , 60 ], Sri Lanka 62.9% [ 51 ], Pakistan 21.1% [ 31 ], Nepal 76.8% [ 61 ], India 68.5% [ 27 ] and Europe 67.4% [ 62 ]. This might be due to the study participants characteristics like older age and higher fasting blood sugar.…”
Section: Discussionmentioning
confidence: 42%